Determinan minat berwirausaha: Studi pada mahasiswa Fakultas Ekonomi dan Bisnis Islam - Selamat Muliadi; Sri Ndaru Arthawati; Herizal Herizal; Hakim Hakim (Universitas Kristen Maranatha, 2024)
Both in the business and academic worlds, entrepreneurship is currently a topic that attracts attention. Fresh graduates have to start their own business cause in large companies there are fewer job offers. However, the low level of entrepreneurial intentions in society causes limited employment opportunities and increases unemployment rates. The aims of this study were to analyze the influence of entrepreneurship education, family environment, and motivation on entrepreneurial interest in college students. Purposive sampling was the sampling technique employed, and 65 respondents from the Even Semester of the 2024/2025 Academic Year were the samples used in this investigation. Several tests, including the validity, realibility, classic assumption, linear regression, and coefficient of determination tests, were used to analyze the data using IBM SPSS version 20. The findings of this study show that partially, entrepreneurship education, family environment, and motivation have a significant effect on entrepreneurial interest among college students at the Faculty of Economics and Islamic Business, UIN Mataram. Simultaneously, entrepreneurship education, family environment, and motivation together have a significant effect on entrepreneurial interest. In addition to offering an overview of the variables that affect students’ interest in entrepreneurship, the research findings contribute to advance knowledge and pave the way for future studies involving more participants and pertinent variables.